MEDIA AUDIO VISUAL SEBAGAI SARANA PENGENALAN EKSPRESI EMOSI - Henie Kurniawati (Komunika, 2015)
Media can be exploited for various purposes, and each media has its specific characteristics for specific purposes. The messages of emotional expression through audiovisual media can be one means to recognize the competencies of individuals in identifying the emotional expression. The emotional expression is defined as a pattern formed in the facial expression in relation to the types of emotion perceived. There are four types of emotional expressions including feelings of anger, sadness, happiness, and scare. This research was aimed at developing instruments to recognize the emotional expressions by using audio visual media. Subjects involved 32 graduate program students of Faculty of Psychology, Gadjah Mada University, Yogyakarta. Data were collected by using rating scale to recognize the emotional expression(feelings of angry, sad, happy, and scary). Quantitative analysis were used in this research with the result of assessment on raters’ responses as additional data. The results of raters’ average assessment showed that the scenes 1 and 13 indicated the highest score for the expression of angry feeling, the scenes 10 and 14 indicated the highest score for the expression of sadness, scenes 11 and 15 the highest score for the expression of happiness, and scenes 8 and 12 the highest score for the expression of scare. The fragments of the scenes were able to be exploited as instruments successfully passed the selection to recognize the emotional expression.